Curable resin composition, adhesive, adhesive varnish, adhesive film, and cured product

The curable resin composition, featuring an epoxy resin, imide oligomer, and liquid curing agent, addresses the issues of tackiness and heat resistance in existing adhesive technologies, providing secure room-temperature mounting and superior long-term heat resistance.

JP7667633B2Active Publication Date: 2025-04-23SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019109475
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-06-12
Publication Date
2025-04-23
Estimated Expiration
2039-06-12

AI Technical Summary

Technical Problem

Existing curable resin compositions used as adhesives face challenges with inferior tackiness at room temperature, leading to slipping during mounting, and poor long-term heat resistance after curing.

Method used

A curable resin composition combining an epoxy resin with an imide oligomer and a liquid curing agent, where the imide oligomer has a number average molecular weight of 4000 or less, and the liquid curing agent is a liquid acid anhydride or phenolic curing agent, optimizing the content and properties to achieve excellent tackability and heat resistance.

Benefits of technology

The curable resin composition exhibits a tack value of 30 gf/5 mmφ or more at 25°C before curing, allowing for secure mounting at room temperature without slipping, and a 5% weight reduction temperature of 350°C or higher, ensuring excellent long-term heat resistance after curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667633000001
    Figure 0007667633000001
  • Figure 0007667633000002
    Figure 0007667633000002
  • Figure 0007667633000003
    Figure 0007667633000003
Patent Text Reader

Abstract

To provide a curable resin composition that has excellent tackiness before curing and, when used as an adhesive, allows a member to be implemented without a shift at room temperature, and has excellent heat resistance after curing; an adhesive, adhesive varnish, and adhesive film prepared with the curable resin composition; and a cured product of the curable resin composition.SOLUTION: A curable resin composition has a pre-curing tack value at 25°C of 30 gf / 5 mmφ or more and a 5% weight loss temperature of its cured product of 350°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition that has excellent tackiness before curing, that can mount components without misalignment at room temperature when used as an adhesive, and that has excellent long-term heat resistance after curing. The present invention also relates to an adhesive, an adhesive varnish, and an adhesive film made using the curable resin composition, and a cured product of the curable resin composition. [Background technology]

[0002] Curable resins such as epoxy resins, which have low shrinkage and excellent adhesiveness, insulating properties, and chemical resistance, are used in many industrial products. In particular, in electronic device applications, curable resin compositions that provide good results in solder reflow tests for short-term heat resistance and thermal cycle tests for repeated heat resistance are widely used.

[0003] For example, Patent Documents 1 and 2 disclose curable resin compositions containing an epoxy resin and an imide compound as a curing agent. However, such curable resin compositions using an imide compound have a problem in that they are poor in tackiness at room temperature and are prone to misalignment of components when used for mounting at room temperature. Furthermore, in the case of a curable resin composition that exhibits tackiness when heated, there are problems in that the components may become misaligned due to heating, and that the curing of the curable resin progresses during heating, making mounting difficult.

[0004] As a curable resin composition having excellent tackiness at room temperature, for example, an epoxy resin composition containing an epoxy resin having a specific structure is disclosed in Patent Document 3. However, such a curable resin composition has a problem in that the cured product has poor long-term heat resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 61-270852 [Patent Document 2] Special Publication No. 2004-502859 [Patent Document 3] JP 2011-068772 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a curable resin composition that has excellent tackiness before curing, that allows components to be mounted without misalignment at room temperature when used as an adhesive, and that has excellent long-term heat resistance after curing. Another object of the present invention is to provide an adhesive, an adhesive varnish, and an adhesive film that use the curable resin composition, and a cured product of the curable resin composition. [Means for solving the problem]

[0007] The present invention includes a curable resin and a heat curing agent, The curable resin includes an epoxy resin, The heat curing agent contains an imide oligomer and a curing agent that is liquid at 25°C, The imide oligomer has a number average molecular weight of 4000 or less, and the curing agent that is liquid at 25°C includes an acid anhydride-based curing agent that is liquid at 25°C or a phenol-based curing agent that is liquid at 25°C; The curable resin composition has a content of the curing agent that is liquid at 25°C of 20 parts by weight or less per 100 parts by weight of the total of the curable resin and the heat curing agent, a tack value at 25°C before curing of 30 gf / 5 mmφ or more, and a 5% weight loss temperature of the cured product of 350°C or more. The present invention will be described in detail below.

[0008] The present inventors have discovered that a curable resin composition having a tack value at 25°C before curing of a specific value or more and a 5% weight loss temperature of the cured product of a specific temperature or more has excellent tack before curing (B stage), is capable of mounting components without misalignment at room temperature when used as an adhesive, and has excellent long-term heat resistance after curing, which led to the completion of the present invention.

[0009] The curable resin composition of the present invention has a tack value of 30 gf / 5 mmφ or more at 25° C. before curing. Since the tack value at 25° C. before curing is 30 gf / 5 mmφ or more, the curable resin composition of the present invention can mount components without misalignment at room temperature when used as an adhesive. The lower limit of the tack value at 25° C. before curing is preferably 40 gf / mmφ, and more preferably 50 gf / mmφ. Further, although there is no particular preferred upper limit for the tack value at 25° C. before curing, the substantial upper limit is 200 gf / mmφ. In this specification, the term "tack value" refers to a tack value measured using a probe tack measuring device under the following measurement conditions: probe diameter 5 mm, contact speed 0.5 mm / sec, test speed 0.5 mm / sec, contact load 0.05 MPa, and contact time 1 sec. Examples of the probe tack measuring device include a tack tester TAC-2 (manufactured by RHESCA). The tack value is obtained by measuring the tack value of a curable resin composition film obtained by coating the curable resin composition on a substrate film and drying the film on the side opposite to the substrate film.

[0010] The curable resin composition of the present invention has a 5% weight loss temperature of 350° C. or higher. Since the cured product has a 5% weight loss temperature of 350° C. or higher, the curable resin composition of the present invention has excellent long-term heat resistance after curing and can be suitably used as a heat-resistant adhesive. The lower limit of the 5% weight loss temperature of the cured product is preferably 360° C., and more preferably 370° C. There is no particular upper limit to the 5% weight loss temperature of the cured product, but the practical upper limit is 450°C. The 5% weight loss temperature can be determined by performing thermogravimetry using a thermogravimetry device under the condition of a temperature rise rate of 10°C / min from 30°C to 500°C. An example of the thermogravimetry device is TG / DTA6200 (manufactured by Hitachi High-Tech Science Corporation). The cured product for measuring the 5% weight loss temperature can be obtained by coating the curable resin composition on a substrate film, drying the composition, and peeling off the substrate film to prepare a curable resin composition film, and heating the obtained curable resin composition film at 190°C for 1 hour.

[0011] The curable resin composition of the present invention preferably has a glass transition temperature before curing of 25° C. or lower. By having the glass transition temperature before curing of 25° C. or lower, the curable resin composition of the present invention has excellent flexibility and processability before curing. The upper limit of the glass transition temperature before curing is more preferably 20° C. There is no particular preferred lower limit for the glass transition temperature before curing, but the substantial lower limit is -20°C. In this specification, the "glass transition temperature before curing" can be determined from the inflection point of the endothermic peak associated with the glass transition when the curable resin composition film is measured at a temperature rise rate of 10°C / min using a differential scanning calorimeter. Examples of the differential scanning calorimeter include DSC7000 series (manufactured by Hitachi High-Tech Science Corporation). The curable resin composition film can be obtained by coating the curable resin composition on a substrate film, drying it, and peeling off the substrate film.

[0012] The curable resin composition of the present invention preferably has a glass transition temperature of 100° C. or higher. When the cured product has a glass transition temperature of 100° C. or higher, the cured product of the curable resin composition of the present invention has excellent long-term heat resistance. The lower limit of the glass transition temperature of the cured product is more preferably 130° C., and even more preferably 150° C. In addition, the curable resin composition of the present invention preferably has a glass transition temperature of 250° C. or lower. When the cured product has a glass transition temperature of 250° C. or lower, the cured product of the curable resin composition of the present invention has better adhesiveness. The upper limit of the glass transition temperature of the cured product is more preferably 220° C. In this specification, the "glass transition temperature of the cured product" can be determined as the peak temperature of a tan δ curve obtained by measuring the temperature from -0°C to 300°C at a heating rate of 10°C / min, a frequency of 10Hz, and a chuck distance of 24mm using a dynamic viscoelasticity measuring device. Examples of the dynamic viscoelasticity measuring device include Rheovibron dynamic viscoelasticity automatic measuring device DDV-GP series (manufactured by A&D Co., Ltd.). The cured product for measuring the glass transition temperature can be obtained by coating the curable resin composition on a substrate film, drying the composition, and peeling off the substrate film to prepare a curable resin composition film, laminating the obtained curable resin composition film to a thickness of 400μm, and heating the laminated film at 190°C for 1 hour.

[0013] The curable resin composition of the present invention preferably has an initial adhesive strength of 3.4 N / cm or more to polyimide after curing. Since the initial adhesive strength of the cured product to polyimide is 3.4 N / cm or more, the curable resin composition of the present invention can be suitably used as an adhesive for coverlays of flexible printed circuit boards. The initial adhesive strength of the cured product to polyimide is more preferably 4 N / cm or more, and even more preferably 5 N / cm or more. The initial adhesive strength to the polyimide can be measured as the peel strength when a test piece cut to a width of 1 cm is subjected to T-shaped peeling at 25°C and a peeling rate of 20 mm / min using a tensile tester. The test piece is obtained by laminating a polyimide film having a thickness of 50 μm on both sides of a curable resin composition film having a thickness of 20 μm and heating the film at 190°C for 1 hour, and the initial adhesive strength means a value measured within 24 hours after the preparation of the test piece. The curable resin composition film can be obtained by coating the curable resin composition on a substrate film and drying the film. As the polyimide, Kapton 200H (manufactured by Toray DuPont Co., Ltd., surface roughness 0.03 to 0.07 μm) can be used. As the tensile tester, for example, UCT-500 (manufactured by ORIENTEC Co., Ltd.) can be mentioned.

[0014] The curable resin composition of the present invention preferably has an adhesive strength to polyimide of 3.4 N / cm or more after storage at 200°C for 100 hours. Since the adhesive strength to polyimide of the cured product after storage at 200°C for 100 hours is 3.4 N / cm or more, the curable resin composition of the present invention can be suitably used as a heat-resistant adhesive. The adhesive strength to polyimide of the cured product after storage at 200°C for 100 hours is more preferably 4 N / cm or more, and even more preferably 5 N / cm or more. The adhesive strength to polyimide of the cured product after storage at 200°C for 100 hours refers to a value measured by storing a test piece prepared in the same manner as in the above-mentioned method for measuring the initial adhesive strength at 200°C for 100 hours, allowing it to cool to 25°C, and then measuring the value within 24 hours after allowing it to cool in the same manner as in the above-mentioned method for measuring the initial adhesive strength.

[0015] The curable resin composition of the present invention has a minimum melt viscosity in the temperature range of 60°C to 180°C of preferably 10 Pa·s as a lower limit and 1200 Pa·s as an upper limit. When the minimum melt viscosity is 10 Pa·s or more, the curable resin composition of the present invention has excellent low exudation properties when mounting a member. When the minimum melt viscosity is 1200 Pa·s or less, the curable resin composition of the present invention has excellent adhesion and conformability to uneven parts. The minimum melt viscosity is more preferably 20 Pa·s as a lower limit and 1000 Pa·s as an upper limit. The minimum melt viscosity is determined as the lowest viscosity value at 60°C to 180°C when the curable resin composition film is heated at a frequency of 1 Hz and a heating rate of 10°C / min using a rotational rheometer. The curable resin composition film can be obtained by coating the curable resin composition on a substrate film and drying it. Examples of the rotational rheometer include HAAKE MARS series (manufactured by Thermo Fisher Scientific), VAR-100 (manufactured by Rheologica), and ARES (manufactured by TA Instruments).

[0016] In the curable resin composition of the present invention, a method for adjusting the tack value, 5% weight loss temperature, each glass transition temperature, initial adhesive strength to polyimide, adhesive strength after storage at 200°C for 100 hours, and minimum melt viscosity to each range as described above is preferably a method of adjusting the type and content ratio of each component contained in the curable resin composition.

[0017] The curable resin composition of the present invention is preferably a thermosetting resin composition, and more preferably contains a curable resin and a thermosetting agent.

[0018] Examples of the curable resin include epoxy resin, acrylic resin, phenol resin, cyanate resin, isocyanate resin, maleimide resin, benzoxazine resin, silicone resin, fluororesin, polyimide resin, etc. Among them, the curable resin preferably contains an epoxy resin. These curable resins may be used alone or in combination of two or more. In addition, in order to improve the tackiness at room temperature and the processability when processing into a film, the above-mentioned curable resin is preferably liquid or semi-solid at 25°C, and more preferably liquid at 25°C.

[0019] Examples of the epoxy resin include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol S type epoxy resin, 2,2'-diallyl bisphenol A type epoxy resin, hydrogenated bisphenol type epoxy resin, propylene oxide-added bisphenol A type epoxy resin, triazine type epoxy resin, resorcinol type epoxy resin, biphenyl type epoxy resin, sulfide type epoxy resin, diphenyl ether type epoxy resin, dicyclopentadiene type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, naphthylene ether type epoxy resin, phenol novolac type epoxy resin, ortho-cresol novolac type epoxy resin, dicyclopentadiene novolac type epoxy resin, biphenyl novolac type epoxy resin, naphthalene phenol novolac type epoxy resin, glycidyl amine type epoxy resin, alkyl polyol type epoxy resin, rubber modified type epoxy resin, and glycidyl ester compound. Among these, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol E type epoxy resins, resorcinol type epoxy resins, and triazine type epoxy resins are preferred because they have low viscosity and the processability of the resulting curable resin composition at room temperature can be easily adjusted.

[0020] Examples of the heat curing agent include an imide oligomer having an imide skeleton in the main chain and a crosslinkable functional group at the end, an acid anhydride curing agent, a phenolic curing agent, a thiol curing agent, an amine curing agent, a cyanate curing agent, and an active ester curing agent. Among them, the heat curing agent preferably contains an imide oligomer, and more preferably contains a combination of an imide oligomer and a curing agent that is liquid at 25° C. By using a combination of the imide oligomer and the curing agent that is liquid at 25° C., it becomes easier to set the tack value and the 5% weight loss temperature within the above-mentioned ranges.

[0021] The imide oligomer preferably has a structure represented by the following formula (1-1) or (1-2) as the structure containing the crosslinkable functional group. By having the structure represented by the following formula (1-1) or (1-2), the imide oligomer has better reactivity and compatibility with curable resins such as epoxy resins.

[0022] [ka]

[0023] In formula (1-1) and formula (1-2), A is a tetravalent group represented by the following formula (2-1) or formula (2-2); in formula (1-1), B is a divalent group represented by the following formula (3-1) or formula (3-2); and in formula (1-2), Ar is an optionally substituted divalent aromatic group.

[0024] [ka]

[0025] In formula (2-1) and formula (2-2), * is a bonding position, and in formula (2-1), Z is a bond, an oxygen atom, or a divalent hydrocarbon group which may be substituted and which may have an oxygen atom at the bonding position. The hydrogen atoms of the aromatic rings in formula (2-1) and formula (2-2) may be substituted.

[0026] [ka]

[0027] In formula (3-1) and formula (3-2), * is a bonding position, and in formula (3-1), Y is a bond, an oxygen atom, or an optionally substituted divalent hydrocarbon group. The hydrogen atoms of the aromatic rings in formula (3-1) and formula (3-2) may be substituted.

[0028] Moreover, the imide oligomer is preferably an imide oligomer that does not have a siloxane skeleton in its structure, since it can lower the glass transition temperature after curing and can contaminate the adherend, resulting in poor adhesion.

[0029] The number average molecular weight of the imide oligomer is preferably 4000 or less. By having the number average molecular weight of 4000 or less, the cured product of the obtained curable resin composition has excellent long-term heat resistance. The upper limit of the number average molecular weight of the imide oligomer is more preferably 3400, and even more preferably 2800. In particular, the number average molecular weight of the imide oligomer is preferably 900 to 4000 when it has a structure represented by formula (1-1), and is preferably 550 to 4000 when it has a structure represented by formula (1-2). A more preferred lower limit of the number average molecular weight when it has a structure represented by formula (1-1) is 950, and an even more preferred lower limit is 1000. A more preferred lower limit of the number average molecular weight when it has a structure represented by formula (1-2) is 580, and an even more preferred lower limit is 600. In this specification, the "number average molecular weight" is a value obtained by measuring using tetrahydrofuran as a solvent by gel permeation chromatography (GPC) and converting the molecular weight into polystyrene equivalent. Examples of columns used in measuring the number average molecular weight converted into polystyrene equivalent by GPC include JAIGEL-2H-A (manufactured by Japan Analytical Industry Co., Ltd.).

[0030] Specifically, the imide oligomer is preferably an imide oligomer represented by the following formula (4-1), (4-2), (4-3), or (4-4), or an imide oligomer represented by the following formula (5-1), (5-2), (5-3), or (5-4).

[0031] [ka]

[0032] In formulae (4-1) to (4-4), A is a tetravalent group represented by the following formula (6-1) or formula (6-2), and in formulae (4-1), (4-3), and (4-4), A may be the same or different. In formulae (4-1) to (4-4), B is a divalent group represented by the following formula (7-1) or formula (7-2), and in formulae (4-3) and (4-4), B may be the same or different. In formula (4-2), X is a hydrogen atom, a halogen atom, or an optionally substituted monovalent hydrocarbon group, and in formula (4-4), W is a hydrogen atom, a halogen atom, or an optionally substituted monovalent hydrocarbon group.

[0033] [ka]

[0034] In formulae (5-1) to (5-4), A is a tetravalent group represented by the following formula (6-1) or (6-2), and in formulae (5-3) and (5-4), A may be the same or different. In formulae (5-1) to (5-4), R is a hydrogen atom, a halogen atom, or an optionally substituted monovalent hydrocarbon group, and in formulae (5-1) and (5-3), R may be the same or different. In formulae (5-2) and (5-4), W is a hydrogen atom, a halogen atom, or an optionally substituted monovalent hydrocarbon group, and in formulae (5-3) and (5-4), B is a divalent group represented by the following formula (7-1) or (7-2).

[0035] [ka]

[0036] In formula (6-1) and formula (6-2), * is a bonding position, and in formula (6-1), Z is a bond, an oxygen atom, or a divalent hydrocarbon group which may be substituted and which may have an oxygen atom at the bonding position. The hydrogen atoms of the aromatic rings in formula (6-1) and formula (6-2) may be substituted.

[0037] [ka]

[0038] In formula (7-1) and formula (7-2), * is a bonding position, and in formula (7-1), Y is a bond, an oxygen atom, or an optionally substituted divalent hydrocarbon group. The hydrogen atoms of the aromatic rings in formula (7-1) and formula (7-2) may be substituted.

[0039] Examples of a method for producing an imide oligomer having a structure represented by the above formula (1-1) include a method of reacting an acid dianhydride represented by the following formula (8) with a diamine represented by the following formula (9).

[0040] [ka]

[0041] In formula (8), A is the same tetravalent group as A in the above formula (1-1).

[0042] [ka]

[0043] In formula (9), B is the same divalent group as B in formula (1-1), and R 1 ~R 4are each independently a hydrogen atom or a monovalent hydrocarbon group.

[0044] A specific example of the method for reacting the acid dianhydride represented by the above formula (8) with the diamine represented by the above formula (9) is shown below. First, the diamine represented by the above formula (9) is dissolved in a solvent (e.g., N-methylpyrrolidone, etc.) in which the amic acid oligomer obtained by the reaction is soluble, and the acid dianhydride represented by the above formula (8) is added to the obtained solution and reacted to obtain an amic acid oligomer solution. Next, the solvent is removed by heating or reducing pressure, and the amic acid oligomer is reacted by heating at about 200°C or higher for 1 hour or more. By adjusting the molar ratio of the acid dianhydride represented by the above formula (8) and the diamine represented by the above formula (9) and the imidization conditions, an imide oligomer having a desired number average molecular weight and a structure represented by the above formula (1-1) at both ends can be obtained. In addition, by replacing a part of the acid dianhydride represented by the above formula (8) with the acid anhydride represented by the following formula (10), it is possible to obtain an imide oligomer having a desired number average molecular weight, a structure represented by the above formula (1-1) at one end, and a structure derived from the acid anhydride represented by the following formula (10) at the other end. In this case, the acid dianhydride represented by the above formula (8) and the acid anhydride represented by the following formula (10) may be added simultaneously or separately. Furthermore, by replacing a portion of the diamine represented by the above formula (9) with a monoamine represented by the following formula (11), it is possible to obtain an imide oligomer having a desired number average molecular weight, a structure represented by the above formula (1-1) at one end, and a structure derived from the monoamine represented by the following formula (11) at the other end. In this case, the diamine represented by the above formula (9) and the monoamine represented by the following formula (11) may be added simultaneously or separately.

[0045] [ka]

[0046] In formula (10), Ar is an optionally substituted divalent aromatic group.

[0047] [ka]

[0048] In formula (11), Ar is an optionally substituted monovalent aromatic group, and R 5 and R 6 are each independently a hydrogen atom or a monovalent hydrocarbon group.

[0049] Examples of a method for producing an imide oligomer having a structure represented by the above formula (1-2) include a method of reacting an acid dianhydride represented by the above formula (8) with a phenolic hydroxyl group-containing monoamine represented by the following formula (12).

[0050] [ka]

[0051] In formula (12), Ar is an optionally substituted divalent aromatic group, and R 7 and R 8 are each independently a hydrogen atom or a monovalent hydrocarbon group.

[0052] A specific example of the method for reacting the acid dianhydride represented by the above formula (8) with the phenolic hydroxyl group-containing monoamine represented by the above formula (12) is shown below. First, the phenolic hydroxyl group-containing monoamine represented by the above formula (12) is dissolved in a solvent (e.g., N-methylpyrrolidone, etc.) in which the amic acid oligomer obtained by the reaction is soluble, and the acid dianhydride represented by the above formula (8) is added to the obtained solution and reacted to obtain an amic acid oligomer solution. Next, the solvent is removed by heating or reducing pressure, and the amic acid oligomer is reacted by heating at about 200°C or higher for 1 hour or more. By adjusting the molar ratio of the acid dianhydride represented by the above formula (8) and the phenolic hydroxyl group-containing monoamine represented by the above formula (12) and the imidization conditions, an imide oligomer having a desired number average molecular weight and a structure represented by the above formula (1-2) at both ends can be obtained. In addition, by replacing a part of the phenolic hydroxyl group-containing monoamine represented by the above formula (12) with the monoamine represented by the above formula (11), it is possible to obtain an imide oligomer having a desired number average molecular weight, a structure represented by the above formula (1-2) at one end, and a structure derived from the monoamine represented by the above formula (11) at the other end. In this case, the phenolic hydroxyl group-containing monoamine represented by the above formula (12) and the monoamine represented by the above formula (11) may be added simultaneously or separately.

[0053] Examples of the acid dianhydride represented by the above formula (8) include pyromellitic dianhydride, 3,3'-oxydiphthalic dianhydride, 3,4'-oxydiphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, 4,4'-bis(2,3-dicarboxylphenoxy)diphenyl ether dianhydride, p-phenylene bis(trimellitate anhydride), and 2,3,3',4'-biphenyltetracarboxylic dianhydride. Among these, the acid dianhydride used as the raw material for the imide oligomer is preferably an aromatic acid dianhydride having a melting point of 240°C or less, more preferably an aromatic acid dianhydride having a melting point of 220°C or less, even more preferably an aromatic acid dianhydride having a melting point of 200°C or less, and particularly preferably 3,4'-oxydiphthalic dianhydride (melting point 180°C) or 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride (melting point 190°C), because it has superior solubility and heat resistance. In this specification, the "melting point" refers to a value measured as the endothermic peak temperature when the temperature is increased at 10° C. / min using a differential scanning calorimeter. Examples of the differential scanning calorimeter include EXTEAR DSC6100 (manufactured by SII NanoTechnology Inc.).

[0054] Examples of the diamine represented by the above formula (9) include 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 3,3'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, bis(4-(4-aminophenoxy)phenyl)methane, 2,2-bis(4-(4 4,4'-diamino-3,3'-dihydroxyphenyl ether, bisaminophenylfluorene, bistruidine fluorene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-diamino-3,3'-dihydroxyphenyl ether, 3,3'-diamino-4,4'-dihydroxybiphenyl, 4,4'-diamino-2,2'-dihydroxybiphenyl, and the like. Among these, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 1,3-bis(2-(4-aminophenyl)-2-propyl)benzene, 1,4-bis(2-(4-aminophenyl)-2-propyl)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene are preferred due to their excellent availability, and 1,3-bis(2-(4-aminophenyl)-2-propyl)benzene, 1,4-bis(2-(4-aminophenyl)-2-propyl)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene are more preferred due to their excellent solubility and heat resistance.

[0055] Examples of the acid anhydride represented by the above formula (10) include phthalic anhydride, 3-methylphthalic anhydride, 4-methylphthalic anhydride, 1,2-naphthalic anhydride, 2,3-naphthalic anhydride, 1,8-naphthalic anhydride, 2,3-anthracene dicarboxylic anhydride, 4-tert-butylphthalic anhydride, 4-ethynylphthalic anhydride, 4-phenylethynylphthalic anhydride, 4-fluorophthalic anhydride, 4-chlorophthalic anhydride, 4-bromophthalic anhydride, and 3,4-dichlorophthalic anhydride.

[0056] Examples of the monoamine represented by the above formula (11) include aniline, o-toluidine, m-toluidine, p-toluidine, 2,4-dimethylaniline, 3,4-dimethylaniline, 3,5-dimethylaniline, 2-tert-butylaniline, 3-tert-butylaniline, 4-tert-butylaniline, 1-naphthylamine, 2-naphthylamine, 1-aminoanthracene, 2-aminoanthracene, 9-aminoanthracene, 1-aminopyrene, 3-chloroaniline, o-anisidine, m-anisidine, p-anisidine, 1-amino-2-methylnaphthalene, 2,3-dimethylaniline, 2,4-dimethylaniline, 2,5-dimethylaniline, 3,4-dimethylaniline, 4-ethylaniline, 4-ethynylaniline, 4-isopropylaniline, 4-(methylthio)aniline, and N,N-dimethyl-1,4-phenylenediamine.

[0057] Examples of the phenolic hydroxyl group-containing monoamine represented by the above formula (12) include 3-aminophenol, 4-aminophenol, 4-amino-o-cresol, 5-amino-o-cresol, 4-amino-2,3-xylenol, 4-amino-2,5-xylenol, 4-amino-2,6-xylenol, 4-amino-1-naphthol, 5-amino-2-naphthol, 6-amino-1-naphthol, 4-amino-2,6-diphenylphenol, etc. Among these, 4-amino-o-cresol and 5-amino-o-cresol are preferred because they are easily available and have excellent storage stability and can provide a high glass transition temperature after curing.

[0058] When the imide oligomer is produced by the above-mentioned production method, the imide oligomer is obtained as a mixture (imide oligomer composition) of multiple types of imide oligomers having the structure represented by the above formula (1-1) or multiple types of imide oligomers having the structure represented by the above formula (1-2) with each raw material. Since the imide oligomer composition has an imidization rate of 70% or more, when used as a curing agent, it is possible to obtain a cured product having excellent mechanical strength at high temperatures and long-term heat resistance. The lower limit of the imidization rate of the imide oligomer composition is preferably 75%, and more preferably 80%. There is no particular upper limit of the imidization rate of the imide oligomer composition, but the substantial upper limit is 98%. The above "imidization rate" is measured by the attenuated total reflection method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR), and is calculated based on the 1660 cm -1 The absorbance area of ​​the peak near the peak can be calculated by the following formula. An example of the Fourier transform infrared spectrophotometer is UMA600 (manufactured by Agilent Technologies). Note that the "peak absorbance area of ​​the amic acid oligomer" in the following formula refers to the absorbance area of ​​the amic acid oligomer obtained by reacting an acid dianhydride with a diamine or a phenolic hydroxyl group-containing monoamine and then removing the solvent by evaporation or the like without carrying out an imidization step. Imidization rate (%)=100×(1-(peak absorbance area after imidization) / (peak absorbance area of ​​amic acid oligomer))

[0059] From the viewpoint of solubility when used as a curing agent in a curable resin composition, the imide oligomer composition preferably dissolves in an amount of 3 g or more in 10 g of tetrahydrofuran at 25°C.

[0060] In addition, the imide oligomer preferably has an imide skeleton and an optionally substituted aliphatic diamine residue and / or an optionally substituted aliphatic triamine residue in the main chain, and has a crosslinkable functional group at the end (hereinafter also referred to as "imide oligomer containing aliphatic diamine residue and / or aliphatic triamine residue"). The imide oligomer containing aliphatic diamine residue and / or aliphatic triamine residue has the aliphatic diamine residue and / or the aliphatic triamine residue, and therefore can improve the flexibility and processability before curing of the obtained curable resin composition, as well as the tackiness at room temperature.

[0061] The content of the imide oligomer in the total of 100 parts by weight of the curable resin and the heat curing agent is preferably 20 parts by weight in lower limit and 80 parts by weight in upper limit. By the content of the imide oligomer being within this range, the obtained curable resin composition is more excellent in flexibility and processability before curing, and in heat resistance after curing. The content of the imide oligomer is more preferably 25 parts by weight in lower limit and 75 parts by weight in upper limit. In addition, when the imide oligomer according to the present invention is contained in the above-mentioned imide oligomer composition, the content of the imide oligomer means the content of the imide oligomer composition (when another imide oligomer is used in combination, the total content of the imide oligomer composition and the other imide oligomer).

[0062] Examples of the curing agent that is liquid at 25° C. include liquid acid anhydride curing agents, liquid imidazole curing agents, liquid amine curing agents, liquid phenolic curing agents, etc. Among these, from the viewpoint of long-term heat resistance, acid anhydride curing agents that are liquid at 25° C. or phenolic curing agents that are liquid at 25° C. are preferred. Examples of the acid anhydride curing agent that is liquid at 25°C include methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, alkylated tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, dodecylsuccinic anhydride, dodecenylsuccinic anhydride, methylnadic anhydride, glutaric anhydride, diethylglutaric anhydride, norbornane-2,3-dicarboxylic anhydride, methylnorbornane-2,3-dicarboxylic anhydride, and glycerin bisanhydrotrimellitate monoacetate. Examples of the phenol-based curing agent that is liquid at 25° C. include liquid alkylphenol resin, liquid allylphenol resin, liquid acetylated phenol resin, and the like.

[0063] The preferred lower limit of the content of the curing agent in a liquid state at 25° C. in a total of 100 parts by weight of the curable resin and the heat curing agent is 1 part by weight, and the preferred upper limit is 30 parts by weight. When the content of the curing agent in a liquid state at 25° C. is within this range, the obtained curable resin composition has better tackiness before curing and long-term heat resistance of the cured product. The more preferred lower limit of the content of the curing agent in a liquid state at 25° C. is 2 parts by weight, and the more preferred upper limit is 20 parts by weight.

[0064] The curable resin composition of the present invention preferably contains a curing accelerator. By containing the curing accelerator, the curing time can be shortened and the productivity can be improved.

[0065] Examples of the curing accelerator include imidazole-based curing accelerators, tertiary amine-based curing accelerators, phosphine-based curing accelerators, photobase generators, sulfonium salt-based curing accelerators, etc. Among these, from the viewpoints of storage stability and curability, imidazole-based curing accelerators and phosphine-based curing accelerators are preferred. The above curing accelerators may be used alone or in combination of two or more kinds.

[0066] The content of the curing accelerator is preferably 0.5% by weight or less based on the total weight of the curable resin, the heat curing agent, and the curing accelerator. By having the content of the curing accelerator of 0.5% by weight or more, the effect of shortening the curing time is more excellent. The more preferable lower limit of the content of the curing accelerator is 0.8% by weight. From the viewpoint of adhesion and the like, the upper limit of the content of the curing accelerator is preferably 10% by weight, and more preferably 5% by weight.

[0067] The curable resin composition of the present invention may contain an inorganic filler for the purpose of improving resistance to moisture absorption and reflow and plating resistance.

[0068] The inorganic filler is preferably at least one of silica and barium sulfate. By containing at least one of silica and barium sulfate as the inorganic filler, the curable resin composition of the present invention has excellent moisture absorption reflow resistance, plating resistance, and processability.

[0069] Examples of inorganic fillers other than the silica and barium sulfate include alumina, aluminum nitride, boron nitride, silicon nitride, glass powder, glass frit, glass fiber, carbon fiber, and inorganic ion exchangers.

[0070] The inorganic fillers may be used alone or in combination of two or more kinds. The inorganic filler preferably has an average particle size of 50 nm or more and less than 4 μm.

[0071] The content of the inorganic filler is preferably 200 parts by weight per 100 parts by weight of the total of the curable resin and the heat curing agent. By the content of the organic filler being within this range, the cured product of the obtained curable resin composition has excellent moisture absorption reflow resistance and plating resistance while maintaining excellent tackiness. The more preferable upper limit of the content of the inorganic filler is 150 parts by weight.

[0072] The curable resin composition of the present invention may contain a flow control agent for the purposes of improving the coatability onto an adherend in a short period of time and the shape retention. Examples of the flow regulator include fumed silica such as Aerosil, layered silicates, and the like. The flow control agents may be used alone or in combination of two or more kinds. The flow control agent preferably has an average particle size of less than 100 nm.

[0073] The content of the flow regulator is preferably 0.1 parts by weight at the lower limit and 50 parts by weight at the upper limit with respect to 100 parts by weight of the total of the curable resin and the heat curing agent. By setting the content of the flow regulator in this range, the effect of improving the short-term application property to the adherend and the shape retention is excellent. The more preferable lower limit of the content of the flow regulator is 0.5 parts by weight, and the more preferable upper limit is 30 parts by weight.

[0074] The curable resin composition of the present invention may contain an organic filler for the purposes of stress relief, toughness, and the like. Examples of the organic filler include silicone rubber particles, acrylic rubber particles, urethane rubber particles, polyamide particles, polyamideimide particles, polyimide particles, benzoguanamine particles, and core-shell particles thereof. Among these, polyamide particles, polyamideimide particles, and polyimide particles are preferred. The organic fillers may be used alone or in combination of two or more kinds.

[0075] The content of the organic filler is preferably 200 parts by weight per 100 parts by weight of the total of the curable resin and the heat curing agent. By setting the content of the organic filler within this range, the cured product of the obtained curable resin composition has excellent toughness while maintaining excellent adhesiveness. The more preferable upper limit of the content of the organic filler is 150 parts by weight.

[0076] The curable resin composition of the present invention may contain a flame retardant. Examples of the flame retardant include boehmite-type aluminum hydroxide, metal hydrates such as aluminum hydroxide and magnesium hydroxide, halogen-based compounds, phosphorus-based compounds, nitrogen compounds, etc. Among these, boehmite-type aluminum hydroxide is preferred. The flame retardants may be used alone or in combination of two or more kinds.

[0077] The content of the flame retardant is preferably 200 parts by weight per 100 parts by weight of the total of the curable resin and the heat curing agent. By the content of the flame retardant being within this range, the obtained curable resin composition has excellent flame retardancy while maintaining excellent adhesiveness, etc. The more preferable upper limit of the content of the flame retardant is 150 parts by weight.

[0078] The curable resin composition of the present invention may contain a thermoplastic resin within a range that does not impair the object of the present invention. By using the thermoplastic resin, the curable resin composition of the present invention has excellent flow properties, and is more easily able to achieve both filling properties and exudation prevention properties during thermocompression bonding, and has excellent flex resistance after curing.

[0079] Examples of the thermoplastic resin include polyimide resin, acrylic resin, phenoxy resin, polyamide resin, polyamideimide resin, polyvinyl acetal resin, etc. Among these, polyimide resin and phenoxy resin are preferred from the viewpoints of long-term heat resistance and ease of handling. The above thermoplastic resins may be used alone or in combination of two or more kinds.

[0080] The number average molecular weight of the thermoplastic resin is preferably 3000 at the lower limit and 100,000 at the upper limit. When the number average molecular weight of the thermoplastic resin is within this range, the resulting curable resin composition has better flow properties and bending resistance after curing. The number average molecular weight of the thermoplastic resin is more preferably 5000 at the lower limit and 50,000 at the upper limit.

[0081] The content of the thermoplastic resin is preferably 60 parts by weight per 100 parts by weight of the total of the curable resin and the heat curing agent (and the curing accelerator if the curing accelerator is contained). By making the content of the thermoplastic resin 60 parts by weight or less, the obtained curable resin composition has better adhesion and long-term heat resistance. The more preferable upper limit of the content of the thermoplastic resin is 50 parts by weight.

[0082] The curable resin composition of the present invention may contain a reactive diluent within a range that does not impair the object of the present invention. From the viewpoint of adhesive reliability, the reactive diluent is preferably one having two or more reactive functional groups in one molecule.

[0083] The curable resin composition of the present invention may further contain additives such as a coupling agent, a dispersant, a storage stabilizer, a bleeding inhibitor, a fluxing agent, and a leveling agent.

[0084] Examples of the method for producing the curable resin composition of the present invention include a method of mixing a curable resin, a heat curing agent, a curing accelerator, etc., using a mixer. Examples of the mixer include a homodisper, a universal mixer, a Banbury mixer, and a kneader.

[0085] The curable resin composition of the present invention can be used in a wide range of applications, but is particularly suitable for electronic material applications that require high long-term heat resistance. For example, it can be used as a die attachment agent for aviation and in-vehicle electric control units, and power devices using SiC and GaN. It can also be used as an adhesive for printed wiring boards, coverlay adhesive for flexible printed circuit boards, copper-clad laminates, semiconductor bonding adhesives, interlayer insulating materials, prepregs, LED sealants, structural material adhesives, and power overlay package adhesives. In particular, it is preferably used for adhesive applications. An adhesive containing the curable resin composition of the present invention is also one aspect of the present invention. In addition, an adhesive varnish containing the curable resin composition of the present invention and a solvent is also one aspect of the present invention.

[0086] From the viewpoints of coatability, storage stability, and the like, the solvent is preferably one having a boiling point of less than 200°C. Examples of the solvent having a boiling point of less than 200° C. include alcohol-based solvents, ketone-based solvents, ester-based solvents, hydrocarbon-based solvents, halogen-based solvents, ether-based solvents, and nitrogen-containing solvents. Examples of the alcohol solvent include methanol, ethanol, isopropyl alcohol, normal propyl alcohol, isobutyl alcohol, normal butyl alcohol, tertiary butyl alcohol, and 2-ethylhexanol. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl propyl ketone, diisobutyl ketone, cyclohexanone, methylcyclohexanone, and diacetone alcohol. Examples of the ester solvent include methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, methoxybutyl acetate, amyl acetate, n-propyl acetate, isopropyl acetate, methyl lactate, ethyl lactate, and butyl lactate. Examples of the hydrocarbon solvent include benzene, toluene, xylene, normal hexane, isohexane, cyclohexane, methylcyclohexane, ethylcyclohexane, isooctane, normal decane, and normal heptane. Examples of the halogen-based solvent include dichloromethane, chloroform, and trichloroethylene. Examples of the ether solvents include diethyl ether, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, diisopropyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol monotertiary butyl ether, propylene glycol monomethyl ether propionate, 3-methoxybutanol, diethylene glycol dimethyl ether, anisole, and 4-methylanisole. Examples of the nitrogen-containing solvent include acetonitrile, N,N-dimethylformamide, and N,N-dimethylacetamide. Among these, from the viewpoints of handling property, solubility of the imide oligomer, etc., at least one solvent selected from the group consisting of ketone solvents having a boiling point of 60° C. or higher, ester solvents having a boiling point of 60° C. or higher, and ether solvents having a boiling point of 60° C. or higher is preferred. Examples of such solvents include methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, isobutyl acetate, 1,4-dioxane, 1,3-dioxolane, tetrahydrofuran, cyclohexanone, methylcyclohexanone, diethylene glycol dimethyl ether, anisole, etc. The above "boiling point" refers to a value measured under a condition of 101 kPa, or a value converted to 101 kPa using a boiling point conversion chart or the like.

[0087] The preferred lower limit of the content of the solvent in the adhesive varnish of the present invention is 20% by weight, and the preferred upper limit is 90% by weight. By having the content of the solvent in this range, the adhesive varnish of the present invention has better coatability, etc. The more preferred lower limit of the content of the solvent is 30% by weight, and the more preferred upper limit is 80% by weight.

[0088] The curable resin composition of the present invention is applied onto a substrate film and dried to obtain a curable resin composition film composed of the curable resin composition of the present invention, and the curable resin composition film can be cured to obtain a cured product. The curable resin film can be suitably used as an adhesive film. An adhesive film having an adhesive layer containing the curable resin composition of the present invention is also one of the present inventions. A cured product of the curable resin composition of the present invention also constitutes the present invention. Effect of the Invention

[0089] According to the present invention, it is possible to provide a curable resin composition that has excellent tackiness before curing, that allows components to be mounted without misalignment at room temperature when used as an adhesive, and that has excellent long-term heat resistance after curing. Also, according to the present invention, it is possible to provide an adhesive, an adhesive varnish, and an adhesive film each using the curable resin composition, and a cured product of the curable resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0091] (Synthesis Example 1 (Preparation of Imide Oligomer Composition A)) 104 parts by weight of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride (Tokyo Chemical Industry Co., Ltd.) was dissolved in 300 parts by weight of N-methylpyrrolidone (Fujifilm Wako Pure Chemical Industries, Ltd., "NMP"). A solution of 56.8 parts by weight of dimer diamine Priamine 1073 (Croda) diluted with 100 parts by weight of N-methylpyrrolidone was added to the obtained solution, and the mixture was stirred at 25°C for 2 hours to react, thereby obtaining an amic acid oligomer solution. After removing N-methylpyrrolidone from the obtained amic acid oligomer solution under reduced pressure, the mixture was heated at 300°C for 2 hours to obtain an imide oligomer composition A (imidization rate 93%). In addition, 1 By H-NMR, GPC, and FT-IR analyses, it was found that the imide oligomer composition A had the above formula ( 4 -1) or ( 4 -3) The part corresponding to A in 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic acid residue and , B The part that corresponds to Dimer diamine residue An imide oligomer containing an aliphatic diamine residue, having a structure represented by the formula: The imide oligomer composition A had a number average molecular weight of 2,200.

[0092] (Synthesis Example 2 (Preparation of Imide Oligomer Composition B)) An imide oligomer composition B (imidization rate 95%) was obtained in the same manner as in Synthesis Example 1, except that 62.0 parts by weight of 3,4'-oxydiphthalic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., "3,4'-ODPA") was used instead of 104 parts by weight of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride. In addition, 1 By H-NMR, GPC, and FT-IR analysis, it was found that the imide oligomer composition B has the above formula ( 4 -1) or ( 4 -3) The part corresponding to A in 3,4'-oxydiphthalic acid residue and , B The part that corresponds to Dimer diamine residue An imide oligomer containing an aliphatic diamine residue, having a structure represented by the formula: The imide oligomer composition B had a number average molecular weight of 1,500.

[0093] (Synthesis Example 3 (Preparation of Imide Oligomer Composition C)) 17.8 parts by weight of diethyltoluenediamine (Mitsui Fine Chemicals, "Ethacure 100") was dissolved in 300 parts by weight of N-methylpyrrolidone (Fujifilm Wako Pure Chemical Industries, Ltd., "NMP"). 62.0 parts by weight of 3,4'-oxydiphthalic dianhydride (Tokyo Chemical Industry Co., Ltd., "3,4'-ODPA") was added to the obtained solution, and the mixture was stirred at 25°C for 2 hours to react, thereby obtaining an amic acid oligomer solution. After removing N-methylpyrrolidone from the obtained amic acid oligomer solution under reduced pressure, the mixture was heated at 300°C for 2 hours to obtain an imide oligomer composition C (imidization rate 92%). In addition, 1 By H-NMR, GPC, and FT-IR analyses, it was confirmed that the imide oligomer composition C contained an aromatic diamine residue-containing imide oligomer. The aromatic diamine residue-containing imide oligomer was represented by the above formula ( 4 -1) or ( 4 It was confirmed that the imide oligomer composition C had a structure in which the moiety corresponding to A in -3) was a 3,4'-oxydiphthalic dianhydride residue and the moiety corresponding to B was a diethyltoluenediamine residue. The number average molecular weight of the imide oligomer composition C was 1,000.

[0094] (Examples 1 to 7, Comparative Examples 1 and 2) According to the compounding ratios shown in Table 1, each material was stirred and mixed to prepare each of the curable resin compositions of Examples 1 to 7 and Comparative Examples 1 and 2. In Table 1, "RIKACID TH" is 1,2,3,6-tetrahydrophthalic anhydride, "MEH-8000H" is liquid allyl group-containing phenolic resin, "HN-2000" is a mixture of 3-methyl-1,2,3,6-tetrahydrophthalic anhydride and 4-methyl-1,2,3,6-tetrahydrophthalic anhydride. In addition, in Table 1, "YH-307" is 4-methylcyclohexane-1,2-dicarboxylic anhydride. Furthermore, in Table 1, "RIKACID MTA-15" is a mixture of glycerin bisanhydrotrimellitate monoacetate and alicyclic dicarboxylic anhydride. Each of the obtained curable resin compositions was applied onto a substrate PET film to a thickness of about 20 μm and dried to produce a curable resin composition film on the substrate PET film.

[0095] (Tack value at 25°C before curing) For each of the obtained curable resin composition films, the tack value at 25° C. was measured using the surface opposite to the substrate PET film. The tack value was measured using a probe tack measurement device (tack tester TAC-2 (manufactured by RHESCA)) under the following measurement conditions: probe diameter 5 mm, contact speed 0.5 mm / sec, test speed 0.5 mm / sec, contact load 0.05 MPa, contact time 1 sec, and measurement temperature 25° C. The results are shown in Table 1.

[0096] (5% weight loss temperature of cured product) The substrate PET film was peeled off from each of the obtained curable resin composition films, and the films were heated at 190° C. for 1 hour to obtain a cured product. The 5% weight loss temperature of the resulting cured product was measured using a thermogravimetric analyzer (Hitachi High-Tech Science Corporation, "TG / DTA6200") in the temperature range of 30° C. to 500° C. at a temperature increase rate of 10° C. / min. The results are shown in Table 1.

[0097] (glass transition temperature before curing) The PET film substrate was peeled off from each of the obtained curable resin composition films, and the glass transition temperature was determined from the inflection point of the endothermic peak associated with the glass transition when the measurement was performed at a temperature rise rate of 10° C. / min using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, "DSC7000 series"). The results are shown in Table 1.

[0098] (Glass transition temperature of the cured product) The substrate PET film was peeled off from each of the obtained curable resin composition films, and laminated using a laminator to obtain a laminated film with a thickness of 400 μm. The obtained laminated film was cured by heating at 190 ° C for 1 hour to produce a cured product. The obtained cured product was heated from 0 ° C to 300 ° C at a heating rate of 10 ° C / min, a frequency of 10 Hz, and a chuck distance of 24 mm using a dynamic viscoelasticity measuring device (manufactured by A & D Co., Ltd., "Leovibron DDV-25GP"), and the peak temperature of the tan δ curve obtained when the temperature was increased from 0 ° C to 300 ° C was determined as the glass transition temperature. The results are shown in Table 1.

[0099] (Adhesion strength of cured product to polyimide) The PET substrate film was peeled off from the obtained curable resin composition film, and a 50 μm thick polyimide film (manufactured by Toray DuPont Co., Ltd., "Kapton 200H") was laminated to both sides of the curable resin composition film while heating it to 80 ° C. using a laminator. The curable resin composition film was cured by heat pressing under conditions of 190 ° C., 3 MPa, and 1 hour, and then cut into a width of 1 cm to obtain a test piece. For the test piece within 24 hours after preparation, a T-shaped peel was performed at 25 ° C. at a peeling speed of 20 mm / min using a tensile tester (manufactured by ORIENTEC Co., Ltd., "UCT-500") to measure the initial adhesive strength. In addition, a test piece prepared in the same manner was stored at 200 ° C. for 100 hours, and then allowed to cool to 25 ° C., and the adhesive strength of the test piece within 24 hours after cooling was measured in the same manner as the initial adhesive strength. The initial adhesive strength and the adhesive strength after storage at 200°C for 100 hours were evaluated as follows: if the adhesive strength was 6.0 N / cm or more, it was marked "◎", if it was 3.4 N / cm or more but less than 6.0 N / cm, it was marked "○", and if it was less than 3.4 N / cm, it was marked "×".

[0100] <Evaluation> The curable resin composition films obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Table 1.

[0101] (Room temperature mounting) The PET base film was peeled off from each of the curable resin composition films obtained in the Examples and Comparative Examples, and a 50 μm thick polyimide film (Toray DuPont Co., Ltd., "Kapton 200H") was attached to one side of the curable resin composition film using a laminator while heating to 80° C. A silicon chip (5 mm×5 mm square, 100 μm thick) was pressed against the exposed surface of the curable resin composition on the side opposite to the polyimide film at 25° C. and 20 N for 1 second using a flip chip bonder (Toray Engineering Co., Ltd., "FC3000") to obtain a silicon chip mounted assembly. Mountability at room temperature was evaluated according to the following criteria. The case where the silicon chip does not shift out of position even when the obtained mounted body is tilted 90 degrees, and 80% or more of the silicon chip area is sufficiently coated when observed from the polyimide side was marked as "◎". The case where the silicon chip does not shift out of position even when the obtained mounted body is tilted 90 degrees, and 50% to less than 80% of the silicon chip area is coated when observed from the polyimide side was marked as "○". The case where the silicon chip does not shift out of position even when the obtained mounted body is tilted 90 degrees, and less than 50% of the silicon chip area is coated when observed from the polyimide side was marked as "△". The case where the silicon chip shifts out of position or falls off when the obtained mounted body is tilted 90 degrees was marked as "X".

[0102] (Long term heat resistance) The substrate PET film was peeled off from each of the curable resin composition films obtained in the Examples and Comparative Examples, and a 20 μm-thick polyimide film ("Kapton V" manufactured by Toray DuPont Co., Ltd.) was laminated on both sides, cured by heating at 190° C. for 1 hour, and then heat-treated for 1000 hours at 175° C. The laminate of the cured product of the curable resin composition and the polyimide film after the heat treatment was aligned in a semicircular shape around a cylinder with a diameter of 5 mm or 3 mm at room temperature, and the state of the laminate was then visually observed. The long-term heat resistance was evaluated as follows: "O" if no cracks or breaks were found when the laminate was fitted in a semicircle around a 3 mm cylinder; "△" if no cracks or breaks were found when the laminate was fitted in a semicircle around a 5 mm cylinder but cracks or breaks were found when the laminate was fitted in a semicircle around a 3 mm cylinder; and "X" if cracks or breaks were found when the laminate was fitted in a semicircle around a 5 mm cylinder.

[0103] [Table 1] [Industrial Applicability]

[0104] According to the present invention, it is possible to provide a curable resin composition that has excellent tackiness before curing, that allows components to be mounted without misalignment at room temperature when used as an adhesive, and that has excellent long-term heat resistance after curing. Also, according to the present invention, it is possible to provide an adhesive, an adhesive varnish, and an adhesive film each using the curable resin composition, and a cured product of the curable resin composition.

Claims

1. Contains a hardenable resin and a heat curing agent, The curable resin includes an epoxy resin, The thermal curing agent includes an imide oligomer and a curing agent that is liquid at 25°C. The imide oligomer has a number average molecular weight of 4000 or less, The curing agent that is liquid at 25° C. includes an acid anhydride-based curing agent that is liquid at 25° C. or a phenol-based curing agent that is liquid at 25° C., The content of the curing agent that is liquid at 25° C. is 20 parts by weight or less in a total of 100 parts by weight of the curable resin and the heat curing agent, A curable resin composition having a tack value at 25°C before curing of 30 gf / 5 mmφ or more and a 5% weight loss temperature of the cured product of 350°C or more.

2. 2. The curable resin composition according to claim 1, which has a glass transition temperature before curing of 25° C. or lower and a glass transition temperature of the cured product of 100° C. or higher.

3. 3. The curable resin composition according to claim 1, wherein the initial adhesive strength of the cured product to polyimide is 3.4 N / cm or more, and the adhesive strength of the cured product to polyimide after storage at 200°C for 100 hours is 3.4 N / cm or more.

4. An adhesive comprising the curable resin composition according to claim 1 , 2 or 3 .

5. 4. An adhesive varnish comprising the curable resin composition according to claim 1, 2 or 3 and a solvent.

6. An adhesive film having an adhesive layer comprising the curable resin composition according to claim 1 .

7. A cured product of the curable resin composition according to claim 1, 2 or 3.

Citation Information

Patent Citations

  • Semiconductor device

    JP1986270852A

  • Polyimide hybrid adhesive

    JP2004502859A

  • Thermosetting resin composition and its use

    JP2007231125A

  • Epoxy resin composition and adhesive film thereof

    JP2011068772A